1998
DOI: 10.1086/515384
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiology of Congenital Rubella Syndrome in the United States

Abstract: To describe clinical presentation and epidemiology of US infants with congenital rubella syndrome (CRS) and to identify missed opportunities for maternal vaccination, data from CRS cases reported to the National Congenital Rubella Syndrome Registry (NCRSR) from 1985 through 1996 were analyzed. Missed opportunities for maternal vaccination were defined as missed postpartum, premarital, and occupational opportunities, that is, times when rubella vaccination is recommended but was not given. From 1985 through 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…Other common signs were cataract (8 children; 44%), purpura (6 children; 33%) and splenomegaly (6 children; 33%). The proportions of various CRS signs and symptoms identified in Myanmar are similar to those reported in studies from Mexico, 19 Panama 20 and the United States, 21 although surveillance methods varied among studies (Table 4). The proportion of children who were deaf was lower in Myanmar and Mexico but this most likely relates to the younger age at which children were examined and the limited ability to assess hearing loss in very young children in most developing countries.…”
Section: Discussionsupporting
confidence: 71%
“…Other common signs were cataract (8 children; 44%), purpura (6 children; 33%) and splenomegaly (6 children; 33%). The proportions of various CRS signs and symptoms identified in Myanmar are similar to those reported in studies from Mexico, 19 Panama 20 and the United States, 21 although surveillance methods varied among studies (Table 4). The proportion of children who were deaf was lower in Myanmar and Mexico but this most likely relates to the younger age at which children were examined and the limited ability to assess hearing loss in very young children in most developing countries.…”
Section: Discussionsupporting
confidence: 71%
“…1,7 Constatamos em nosso estudo que a rubéola congênita correspondeu a 23,6% dos casos e foi a causa identificável mais expressiva de deficiência auditiva, confirmando estudos já realizados nos países em desenvolvimento. 5,[8][9][10][11] Outras etiologias relevantes foram associações de fatores patogênicos (19,8%) como descritos na Tabela 2 e a meningite foi a etiologia pós-natal mais importante de disacusia sensorioneural. (Tabela 1) A incidência de meningite na literatura varia de 6 a 22%.…”
Section: Resultsunclassified
“…A study in the United States showed that among cases of CRS with missed opportunities for vaccination (including postpartum, premarital, and occupational opportunities), 81% missed postpartum opportunities. 33 To achieve the goal of eradicating rubella, all opportunities of vaccination should be taken to ensure that all susceptible women are vaccinated.…”
Section: Discussionmentioning
confidence: 99%